Enhancing Understanding of Ethical Product Photography: Mitigating Ambiguity in Online Commerce - Mohamad Torik Langlang Buana; Fardinal Fardinal; Deden Tarmidi (Indonesian Journal of Cultural and Community Development, 2023)
In the realm of online commerce, product photography serves as a vital means of introduction and presentation for sellers, significantly impacting the purchasing decisions of potential buyers. High-quality and ethically crafted product photos are not only beneficial to sellers but also uphold principles of transparency and fairness in accordance with Islamic economic ethics. This community engagement initiative aimed to enhance foundational knowledge regarding ethical product photography, ultimately ensuring that product images accurately represent the goods being sold, thus avoiding potential misunderstandings that may arise from misleading visuals in advertisements. The methodology involved educating participants about the concept of "gharar" (ambiguity) as it pertains to product images used in advertising. The findings indicate that participants gained a better understanding of both photography techniques and the ethical implications of ambiguity, thereby contributing to more honest and transparent online trading practices. This research underscores the importance of aligning e-commerce practices with ethical principles and highlights the potential for improved consumer trust and satisfaction in online marketplaces. Highlight: Impact of Product Photography: Product images play a crucial role in online commerce, influencing the purchasing decisions of potential buyers and serving as a key introduction for sellers. Ethical Considerations: High-quality and ethically crafted product photos not only benefit sellers but also adhere to principles of transparency and fairness, aligning with Islamic economic ethics. Community Engagement for Ethical Photography: This initiative aims to educate participants on the importance of ethical product photography, ensuring accurate representation of goods and preventing potential misunderstandings from misleading visuals in advertisements. Keyword: Online Commerce, Product Photography, Ethical Practices, Transparency, Islamic Economic Ethics